Effect of clinical whole exome sequencing in aetiological investigation and reproductive risk prediction for a couple with monogenic inherited diseases - Wang, Yanan; Chai, Yuqiong; Wang, Jieqiong; Gao, Mingya; Zang, Weiwei; Chang, Yujie (Frontiers in Genetics, 2024)
Objective: To determine the genetic causes of monogenic inherited diseases in a couple using clinical whole exome sequencing (WES) and advise on their reproductive choices. Methods: WES was applied to a couple seeking reproductive advice, the female with short stature and the male with congenital cataracts. Results:(1) The woman exhibited a 13.8 Kb heterozygous deletion at chrX: 591590-605428 (hg19). This region corresponds to exons 2-6 of the short-stature homeobox-containing (SHOX) gene (NM000451). Associated diseases involving the SHOX gene range from severe Leri-Weill dyschondrosteosis to mild nonspecific short stature. Meanwhile, further validation using a quantitative reverse transcription polymerase chain reaction assay confirmed the heterozygous deletion of the SHOX gene in the proband, as well as other family members with similar clinical characteristics (the proband's mother, aunt, and cousin). Multiple pathogenic reports of this variant have been included in the HGMD database. Per the American College of Medical Genetics and Genomics (ACMG) classification criteria, this deletion is classified as pathogenic. (2) For the male patient, a heterozygous variant was detected in the CRYBB3 gene: NM004076: c.226G>A (p.Gly76R). Variants in the CRYBB3 gene can cause Cataract 22 (OMIM: 609741). At present, this variant locus is not included in databases such as the gnomAD, while both SIFT and PolyPhen2 deem this locus 'damaging'. Moreover, further validation by Sanger sequencing confirmed that the variant was inherited from the male patient's mother, who also had cataracts.According to ACMG standards and guidelines, the c.226G>A (p.Gly76Arg) variant in the CRYBB3 gene is classified as having 'uncertain significance'. Conclusion: WES identified pathogenic variants in both individuals, suggesting a 25% chance of a healthy child naturally. Third-generation assisted reproductive techniques are recommended to minimize the risk of affected offspring.